Studies on Effect of Mannan oligosaccharides, β-glucan and their Combination on Immune Status and Litter Condition of Broilers Reared under Hot Climatic Condition - Taye, Kushal; Nikam, M. G.; Dhumal, M. V.; Khose, K. K.; Munde, V. K.; Gaikwad, S. S. (International Journal of Livestock Research, 2021)
An experiment was conducted to evaluate the immune status litter condition of broilers by supplementation of mannan oligosaccharides (MOS), β-glucan and their combination. 320 one day old straight run Vencobb400 chicks were weighed and distributed randomly into four treatment groups viz, A, B, C and D with four replicates consists of 20 chicks in each replicate. Treatment group A was serving as control without supplementation of MOS and β-glucans. Supplementation of β-glucans @5g/100kg and MOS@ 50g/100kg of feed was done in treatment group B and C respectively. The treatment D was a combination of treatment B and C. The results revealed non-significant influence of supplementation of MOS, β-glucans and their combination on Ranikhet Disease (RD) titre at 21st and 42nd days of age. There were non-significant differences with pH and the litter moisture. It may be concluded that the supplementation of β-glucans, MOS and their combination did not record any adverse effect on litter quality and RD titer.